METHODS OF EFFECTIVE TEACHING OF FOREIGN LANGUAGES IN A SHORT PERIOD OF TIME IN FINLAND AND GREAT BRITAIN (Journal of Universal Science Research, 2023)
Modern English Language teaching methods are considered in the article. Special attention is paid to the cross-cultural competence.